ポーラー パトロール バルーン ニ ヨル 1991 ネン ノ オゾンホール カンソク ケイカク - 神沢, 博; カンザワ, ヒロシ; 近藤, 豊; コンドウ, ユタカ; Kanzawa, Hiroshi; Kondo, Yutaka (1991)
P(論文) 第32次南極地域観測隊によって実施される三つのポーラー・パトロール・バルーン(PPB)実験のうちの一つとして, 昭和基地(69°S, 40°E)から1991年9月に, 南極オゾンホールとして知られる南極大陸上空のオゾン層の破壊現象を観測するための気球が放球される。オゾン, エアロゾル, 温度のその場(in situ)での観測を, 南極大陸上空50hPa(約18km)を浮遊する気球の軌跡に沿って, 約10日間行う。この観測の動機は以下の通りである : 極域成層圏雲(PSCs)は冷たい極域下部成層圏で形成されるエアロゾルから成ること;冬の後期あるいは春の初期のオゾンの減少(南極オゾンホールの一側面)が, PSCs表面で起こる不均一系化学反応過程によると考えられていること。オゾン減少は50hPaの高度で顕著であり, PPBはこの高度を浮遊して, ラグランジュ型の観測を行うことができる。従って, PPBによるオゾン観測は, オゾンの化学的ソース/シンクの大きさを, ほかの型の観測に比べてより直接的に測ることができるという利点を持つ。エアロゾル観測器は, エアロゾルの粒径分布を, 0.4-10μmの間を7分割して測るので, PSCsの微物理および化学についての詳細な情報を与える。データ取得および気球位置決定はARGOSシステムを使用して行う。ゼロプレッシャー気球の高度は, オートバラストシステムによってほぼ一定高度に維持される。 Among the three Polar Patrol Balloon (PPB) experiments planned in the course of the 32nd Japanese Antarctic Research Expedition, one balloon will be launched from Syowa Station (69°S, 40°E) in September 1991 to observe depletion of the ozone layer over Antarctica-the so-called Antarctic ozone hole. In situ measurements will be made of ozone, aerosol, and temperature along the track of the balloon around the 50hPa level (∿18km) for about 10 days. The motivation for this exercise is as follows : Polar Stratospheric Clouds (PSCs) consist of aerosols which are formed in the cold polar lower stratosphere; the decrease of ozone in the Antarctic lower stratosphere in late winter and early spring, which is an aspect of the Antarctic ozone hole, is believed to be due to heterogeneous chemical processes occurring on the surface of PSCs. The PPB observation is a Lagrangian type observation, and it will be held around the 50hPa level where the ozone decreases most. Consequently, the ozone concentration measurement has the advantage that it will be able to detect the in situ chemical budget of ozone more directly than other types of observation. The aerosol instrument measures aerosol concentrations in the diameter range of 0.4-10 micron meters, devided into 7 classes to give detailed information on the microphysics and chemistry of PSCs. Data acquisition and balloon positioning will utilize the ARGOS ...